Disruptors' dilemma? Thailand's 2020 Gen Z protests. Issue 2 (3rd April 2021) - McCargo, Duncan
ABSTRACT: This article offers a preliminary analysis of the hundreds of youth-inspired mass protests staged in Thailand during 2020. It argues that while calling for reforms and flirting with revolutionary rhetoric, the protestors lacked a clear programmatic agenda and were primarily engaged in disrupting dominant narratives about the country's politics, especially in relation to the previously taboo question of the political role of the monarchy. Despite the ad hoc and sometimes incoherent nature of the protests, the students mounted a dramatic challenge to Thailand's ruling elite. Ultimately, the conflict exemplified a generational divide: people from Generation Z, aged under 25, have radically different understandings of power, deference and legitimacy from older population groups. Whatever happens to the protest movement in the short term, the demonstrators have made a decisive break with the old social consensus that existed during the long reign of the late King Bhumibol (1946–2016).